Determinan kinerja pegawai badan pengembangan sumber daya manusia dimediasi oleh motivasi kerja - Asraf Asraf; Hasnia Hasnia; Dedy Takdir Syaifuddin (Universitas Kristen Maranatha, 2025)
Human resources are responsible for carrying out various tasks and play a pivotal role in fostering organizational progress. Each organization applies different standards in evaluating potential candidates for human resource positions. One of the crucial problems encountered by institutions is the effort to continuously improve employee performance. The enhancement of workforce quality and efficiency can be achieved through training program, career development, and the creation of a supportive work environment on employee performance, with work motivation serving as a mediating variable, at the Human Resource Development Agency of Southeast Sulawesi Province. The study employs a quantitative approach and utilizes regression analysis. The population consisted of all 76 employees of BPSDM, and a purposive sampling technique was used to select 63 respondents based on completed questionnaires. The data were examined using SEM-PLS reveal that human resource development and the work environment exert a positive and significant impact on employee performance. In contrast, work motivation does not demonstrate a significant direct effect on performance. Work motivation acts as a mediating variable in the link between human resource development and performance, effectively bridging this relationship. However, it does not mediate the impact of the work environment on performance. These study findings may serve as a valuable reference for provincial government institutions in their effort to enhance performance, ultimately leading to improvement in the quality of public services delivery to the community.